(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The level of social support of individuals is varied in the community and is determined and influenced by different socio-cultural factors and traditional practices. This study, therefore, examined the religious groups and gender as determinant factors of social support in students. The data was collected from 682 students, comprised of 275 boys and 407 were girls from different colleges in Mysore, Karnataka and the age range of the college students between 16 to 23 years. The social support appraisal scale (SSAS) and socio-demographic data sheet were utilized to elicit the data from the participants. Gathered information was analyzed by applying One-Way ANOVA and Independent sample t-tests. The result indicates that religion emerged as a determinant factor of social support and religion alone has a significant influence on student’s social support. However, there is no significant gender difference found on the social support of college students.